Challenges to Work–Family Balance Among Men in Contemporary Organisations: Implications for Organisational Policy and Practice - Okolie, Ugo Chuks (The Manager Review, 2026)
The challenge of achieving a satisfactory balance between work and family life has become an increasingly significant concern for men in contemporary organisations, as shifting gender roles, economic pressures, and evolving organisational expectations redefine traditional notions of masculinity and breadwinning. Historically, men were perceived primarily as economic providers, with limited scholarly attention paid to their family responsibilities. This study adopts a historical research method, drawing on existing literature, policy documents and longitudinal workplace studies to trace the evolution of men’s work–family roles and organisational responses over time. The study is anchored on Role Strain Theory, which explains how competing demands from work and family roles generate tension, stress and conflict when individuals lack adequate resources or institutional support. Findings reveal that men increasingly experience work–family conflict due to long working hours, rigid organisational cultures, limited access to family-friendly policies and persistent stigma surrounding male caregiving. Despite policy advancements in areas such as parental leave and flexible working, organisational practices often discourage men from utilising these provisions, thereby reinforcing the imbalance. The study concludes that work–family balance challenges among men are not solely individual issues but are deeply embedded in organisational structures, norms and policy implementation gaps. Without intentional organisational reform, these challenges will continue to affect employee wellbeing, job satisfaction and productivity. It is recommended, among others, that organisations actively normalise and encourage men’s participation in family-friendly programmes through inclusive policy design, leadership support and cultural change initiatives that redefine work–family balance as a shared responsibility.